MODERN MODEL OF PRIMARY EDUCATION - M. J. Saidova (Web of Journals Publishing, 2024)
This article describes modern education, its content, the essence of organizing a modern approach to primary education, foreign experience in modern primary education. The content of modern primary education in the education of the USA, Singapore, Finland and Uzbekistan is comparatively analyzed.
Keywords: Future primary school teacher, world experience, modern education, modern approach, oral-visual approach, inquiry approach, Finnish education, Singapore education, O Uzbekistan education, independent education.